2019
DOI: 10.1101/516500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Prediction of Potential Polycomb Response Elements and their Functions

Abstract: The Polycomb-group proteins (PcG) and Trithorax-group proteins (TrxG) are two major epigenetic regulators important for proper differentiation during development (1,2). In Drosophila melanogaster (D. melanogaster), Polycomb response elements (PREs) are short segments of DNA with a high density of binding sites for transcription factors (TFs) that recruit PcG and TrxG proteins to chromatin. Each PRE has a different number of binding sites for PcG and TrxG, and these binding sites have different topological orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Identification of predicted PRE sites was performed exactly as described in (28), using the dm6 genome. As suggested in (28), we use a threshold confidence score of 0.8 to identify the PREs used in the present analysis. A complete list of predicted PREs, with accompanying confidence scores, is shown in file S1.…”
Section: Predictormentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of predicted PRE sites was performed exactly as described in (28), using the dm6 genome. As suggested in (28), we use a threshold confidence score of 0.8 to identify the PREs used in the present analysis. A complete list of predicted PREs, with accompanying confidence scores, is shown in file S1.…”
Section: Predictormentioning
confidence: 99%
“…To identify likely targets of each transcription factor of interest, we drew upon the transcription factor binding site calculations described in (28) in which the motif of each transcription factor was scanned along every base pair of the D. melanogaster dm6 genome using FIMO (71) and the base-pairwise binding results were converted to robust z scores. For each TF, we then considered its regulon to consist of all genes with at least one binding site with z score above a TF-specific threshold within 2-kb upstream of the beginning of the gene.…”
Section: Calculation Of Regulatory Targets Of Transcription Factorsmentioning
confidence: 99%
“…Response Elements (PREs), cis-regulatory sequences to which Polycomb Group Proteins bind in D. melanogaster (Chan et al, 1994) (Müller and Kassis, 2006) . Using a recently developed tool that predicts PRE regions genome-wide (Khabiri and Freddolino, 2019) , we found that Pcl was present in these regions ( Fig. 3D To determine changes in Pcl occupancy with diet, we compared Pcl peaks between flies fed a control and sugar diet.…”
Section: Pcl Chromatin Occupancy Is Redistributed In the High Sugar Ementioning
confidence: 99%
“…Identification of predicted PRE sites was performed exactly as described in (Khabiri and Freddolino, 2019) , using the dm6 genome. As suggested in (Khabiri and Freddolino, 2019) , we use a threshold confidence score of 0.8 to identify the PREs used in the present analysis. A complete list of predicted PREs, with accompanying confidence scores, is shown in supplementary file 1.…”
Section: Predictormentioning
confidence: 99%
See 1 more Smart Citation